Study of Histopathological Pattern of Endometrial Curettings and Healthcare Burden due to Inadequate Samples - Sameen Ejaz, Maryam Ejaz, Umme Kalsoom, Maha Kamran, Deeba Ahsan, Samina Qamar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of different histopathological findings of endometrial curettings presenting to a tertiary care hospital with a special focus on the frequency of inadequate samples which impose a major healthcare burden. Methods: The data of 975 female patients whose EC samples were received in the Pathology Lab of King Edward Medical University (KEMU), Lahore from August 2019- August 2021 was included in this retrospective, descriptive study. A statistical analysis of endometrial findings according to age and their association with histopathological findings was determined. Results: A total of 975 cases were analyzed (average age, 42.95 years). 34.9% had hormone induced change (n=340), 235 had secretory endometrium (24.1%). Next in the list were Chronic Endometritis, proliferative phase and endometrial polyps accounting for 68(7%), 57(5.8%) and 16(1.6%) of the biopsies respectively. 1.6% patients had Endometrioid Carcinoma 16 and 9(0.9%) had Squamous cell carcinoma. 201(20.6%) of the total were inadequate biopsy specimens. There were 28 cases of hyperplasia, half of which were associated with atypia and half were without atypia, i.e., 14(1.4%). Atrophic endometrium and granulomatous inflammation accounted for 3(0.3%) and 2(0.2%) cases respectively. Conclusion: A diverse spectrum of endometrial patterns was observed that included physiological as well as pathological patterns. The pathologies ranged from benign conditions to malignancies. There was a huge frequency of inadequate biopsies that were indicative of wastage of the limited resources of healthcare system.